IMPLEMENTASI INSTRUKSI PRESIDEN NO.3 TAHUN 2003 TENTANG KEBIJAKAN DAN STRATEGI NASIONAL PENGEMBANGAN ELECTRONIC GOVERNMENT DI KABUPATEN SEMARANG - Sinaga, Epiphany; Suwitri, Sri; Mustam, Mochammad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The Progress information technology as well as the potential for extensive use, opening opportunities for access, management and utilization of information in large numbers quickly and accurately. There is also the problem that this aspect of the barrier to the development of e- Government in terms of understanding the implementor of the presidential instruction No. 3 of 2003, the lack of financial resources and human resources, the lack of sharing of information between government agencies and the uneven condition of Semarang Regency environment political, economic and social technology. And the purpose of this research was to describe the implementation of presidential instruction No. 3 of 2003 and to identify aspects that hinder the development of e-Government in Semarang Regency. This research uses qualitative research with purposive technique. Informants are chosen as much as 4 with interviews. Implementation development refers to the theories of Donald Van Meter and Van Horn and Daniel A. Mazmanian Paul A. Sabatier include: implementation of presidential instruction No. 3 of 2003, the characteristics of the policy issues, and environmental policy. The results of this research show that the implementation of presidential instruction No. 3 of 2003 still relatively good. Still the limited financial resources, implementor understanding and human resources as well as unequal conditions of political, economic and social environment and the technology becomes less the maximum factor of results achieved by the Government of Semarang Regency. As for the recommendation on the implementation of this is the increased understanding of the implementor by doing socialization, increased quality and quantity of human resources with skills training in the field of information technology and the consciousness of every Government Agency (SKPD) giving information as up to date in the development of e-Government.